2018
DOI: 10.3390/ijerph15081569
|View full text |Cite
|
Sign up to set email alerts
|

Poor Dietary Habits in Bullied Adolescents: The Moderating Effects of Diet on Depression

Abstract: The prevalence of bullying has increased dramatically during recent years, with numerous negative consequences for the health and quality of life of bullied adolescents. Although negative psychological consequences of this type of situation have been widely investigated, no previous research has evaluated the effects of bullying victimization on dietary habits, and its relationship with psychological outcomes, such as depression. For this reason, the main aim of the present study was to evaluate the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
(63 reference statements)
3
9
0
Order By: Relevance
“…In children and adolescents, high adherence to the MD has been related to better health-related quality of life, academic performance and sleep quality, among others [5,6,7]. During adolescence and adulthood, adherence to the MD has been found to be protective for mood, in general, and for depression in particular [8,9]. In older people, it has been also found that the adoption of this healthy dietary pattern reduces the risk of cardiovascular diseases, as well as cancer, and the incidence of chronic diseases such as Alzheimer’s and Parkinson’s [10,11,12,13], being associated with a higher longevity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In children and adolescents, high adherence to the MD has been related to better health-related quality of life, academic performance and sleep quality, among others [5,6,7]. During adolescence and adulthood, adherence to the MD has been found to be protective for mood, in general, and for depression in particular [8,9]. In older people, it has been also found that the adoption of this healthy dietary pattern reduces the risk of cardiovascular diseases, as well as cancer, and the incidence of chronic diseases such as Alzheimer’s and Parkinson’s [10,11,12,13], being associated with a higher longevity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Sampasa-Kanyinga et al (2014) and Sampasa-Kanyinga and Willmore (2015) reported significant relationships between bullying victimization (both traditional and online), breakfast skipping, and psychological distress among middle school and high school students, indicating that psychological distress mediates the association between victimization and breakfast skipping. As mentioned previously, Albaladejo-Blazquez et al (2018) indicated that some dietary habits were significantly correlated with victimization; nonetheless, eating breakfast regularly was not one of them. The aforementioned studies involve the investigation of children and adolescents; however, to the best of my knowledge, no research has evaluated the breakfast-skipping behaviors of adults and any potential association they may have with bullying victimization.…”
mentioning
confidence: 72%
“…Participants were divided into two groups (high cyber-victimized versus low cyber-victimized) based on their total scores on the CBVQ victimization items; high-victimized reported a score greater than the median value across all male or female respondents and low-victimized reported a score less than or equal to the median value across all male or female respondents (male median = 1; female median = 3). The process used for high vs. low victimized group formation is in line with other studies investigating bullying victimization (Albaladejo-Blazquez et al 2018;Jochman et al 2017). Means and standard deviations for each variable are presented in Table 2 Independent samples t tests for males and females were also conducted to examine the difference between individuals who experience high versus low levels of traditional victimization on the BVQ, CBVQ, PD, and BRFAST scales.…”
Section: Data Screeningmentioning
confidence: 95%
See 2 more Smart Citations